PENGEMBANGAN MEDIA PEMBELAJARAN DIGITAL IPAS BERBASIS KEARIFAN LOKAL MUNA PA'A DENGAN STRATEGI MICROLEARNING UNTUK MENINGKATKAN RETENSI BELAJAR SISWA SD - Ilham, Ilham; Srirahmawati , Ija; Sumiati, Sumiati; Nurmalia, Nurmalia (Jurusan Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to develop a digital Natural and Social Sciences (IPAS) learning media integrating Muna Pa’a local wisdom through a microlearning strategy to enhance students’ learning retention. The research employed a Research and Development (R&D) design with the 4-D model (Define, Design, Develop, and Disseminate). The study involved fourth-grade students at SDN 19 Woja, focusing on the media’s validity, practicality, and effectiveness. The results show that the developed media was rated “Highly Valid” by experts with an average score of 88.33%, “Highly Practical” by teachers (87.67%) and students (90.33%), and “Effective” in improving students’ retention, as indicated by the increase in the average score from 55.2 (pre-test) to 82.5 (post-test). The integration of Muna Pa’a values and microlearning successfully created contextual and engaging digital learning media that enhance memory and cultural understanding. This innovation can be adopted as an alternative solution to improve the quality of IPAS learning in elementary schools.